2022
DOI: 10.14336/ad.2021.1213
|View full text |Cite
|
Sign up to set email alerts
|

Metformin's Mechanisms in Attenuating Hallmarks of Aging and Age-Related Disease

Abstract: Aging is a major global challenge, and there is growing demand for new strategies to address the burden of aging. The intensive search for antiaging agents has led to the discovery of a variety of drugs that promote the extension of healthspan and/or life. Metformin is a safe, effective, and globally affordable antihyperglycemic agent that has gained much attention in recent years as a potential antiaging treatment. Metformin has been shown to significantly delay the onset of age-related diseases and increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 176 publications
0
9
0
Order By: Relevance
“…Acarbose is an inhibitor of alpha-glucosidases, a class of intestinal enzymes necessary to digest carbohydrates [27]. Acarbose exerts anti-inflammatory effects on human monocytic THP-1 cells [28], and Sadagurski et al [29] suggested that acarbose may prolong lifespan in mice by inhibiting age-related hypothalamic inflammation. Metformin appears to exert antiaging actions via multiple mechanisms, including nutrient sensing, DNA repair, oxidative stress, telomere attrition, inflammation, cellular senescence, stem cell decline, and autophagy [30].…”
Section: Longevity Candidatesmentioning
confidence: 99%
“…Acarbose is an inhibitor of alpha-glucosidases, a class of intestinal enzymes necessary to digest carbohydrates [27]. Acarbose exerts anti-inflammatory effects on human monocytic THP-1 cells [28], and Sadagurski et al [29] suggested that acarbose may prolong lifespan in mice by inhibiting age-related hypothalamic inflammation. Metformin appears to exert antiaging actions via multiple mechanisms, including nutrient sensing, DNA repair, oxidative stress, telomere attrition, inflammation, cellular senescence, stem cell decline, and autophagy [30].…”
Section: Longevity Candidatesmentioning
confidence: 99%
“…Its inhibitors (e.g. metformin) could sensitize SnCs while also acting as senomorphics, another class of senotherapeutics capable of altering the composition of the SASP through the modulation of intracellular pathways ( Cheng et al, 2022 ). Molecules with senomorphic properties have become increasingly relevant since signaling mediated by some proteins encoded by oncogenes can also modulate the production of SASP.…”
Section: Senotherapies In Cancer: From Senoprevention To Senolysismentioning
confidence: 99%
“…The neuroprotective effects of metformin have been associated with its ability to induce autophagy [72]. This mechanism involves the activation of 5 AMP-activated protein kinase (AMPK) and the suppression of mTOR signaling, leading to enhanced autophagic processes and facilitating the lysosomal degradation of Aβ [73]. As a result, metformin significantly reduces Aβ levels in the brain.…”
Section: Therapeutic Targeting Of Histone Methylationmentioning
confidence: 99%